Dampak Terapi Antipsikotik terhadap Lama Rawat Inap dan Gejala Eksitasi pada Pasien Skizofrenia - Rahmi Yosmar; Dedy Almasdy; Rahmad Abdillah; Hudiyah Amni (Postgraduate, University of Mataram, 2025)
Schizophrenia is a complex psychiatric disorder treated primarily with antipsychotics, yet their impact on clinical outcomes such as hospital stay and excitement symptoms, measured by the Positive and Negative Syndrome Scale–Excitement Component (PANSS-EC), remains uncertain. This study examined the association between antipsychotic therapy, hospital stay duration, and PANSS-EC scores in patients with schizophrenia. A retrospective, cross-sectional analysis was conducted on 271 patients. Sociodemographic data were analyzed descriptively, and the Kruskal–Wallis test was applied for bivariate analysis across treatment groups. The results showed that patients were predominantly male (72.7%), most frequently diagnosed with paranoid-type schizophrenia (42.8%), and commonly aged 26–35 years (33.9%). No significant differences were found in hospital stay or PANSS-EC scores among the antipsychotic treatment groups. However, gender was significantly associated with PANSS-EC score changes, and schizophrenia subtype correlated with hospital stay duration. Antipsychotic therapy demonstrated no direct association with hospital stay or PANSS-EC outcomes. Instead, demographic and clinical factors, particularly gender and schizophrenia subtype, influenced treatment outcomes. These findings underscore the need for further investigation into patient-specific variables to optimize therapeutic strategies in schizophrenia care.